Measuring in situ Cosmogenic Beryllium-10 and Aluminum-26 in Deglacial Sediment Reveals Limited Erosion Under the Quebec-Labrador Ice Dome, Canada, 2022 - 2024 ... - Cavnar, Peyton; Bierman, Paul; Shakun, Jeremy; Corbett, Lee; Caffe, Marc; Galford, Gillian; LeBlanc, Danielle (NSF Arctic Data Center, 2024)
We know little about the Laurentide Ice Sheet’s erosive behavior prior to the Last Glacial Maximum because, as the ice sheet advanced, it largely eroded evidence of previous glaciations. To understand the erosivity of the eastern portion of the Laurentide Ice Sheet, the Quebec-Labrador Ice Dome, we sampled sand from deglacial features (eskers and deltas) across eastern Canada—a landscape repeatedly overrun by ice. We measured concentrations of 10Be and 26Al in quartz isolated from the sediment and, after correcting for cosmic-ray exposure during the Holocene, used these results to determine nuclide concentrations at the time of deglaciation. To infer sediment sourcing using Beryllium-10 (10Be) and Aluminum-26 (26Al), we collected and analyzed modern river sediment drained from Holocene-exposed landscapes. The mean 10Be concentration in deglacial sediments (n=11) is (1.87 ±1.39) E4 atoms per gram (g-1) and (3.31 ±1.57) E4 atoms g-1 in modern river sediments (n=10). Corrected for Holocene exposure, we ...